MENTAL WELL-BEING IN MEDICAL STUDENTS: DIGITAL AGE STRESSORS AND SUSTAINABLE SOLUTIONS (Asian Journal of Medical Research and Health Sciences, 2026)
Medical students experience significantly higher rates of anxiety, depression, stress, and burnout than their non-medical peers due to the demanding nature of medical education. Academic overload, clinical responsibilities, perfectionism, and stigma surrounding help-seeking contribute to persistent psychological distress, often affecting academic performance and quality of life. The COVID-19 pandemic further intensified these challenges by disrupting traditional learning environments, increasing social isolation, and accelerating reliance on digital platforms. While social media and online learning facilitated academic continuity and peer interaction, excessive digital engagement was associated with information overload, sleep disturbances, fear of missing out, misinformation, and heightened psychological stress. This narrative review examines the evolving mental health challenges faced by medical students in the digital era and highlights the dual role of social media as both a potential stressor and a source of social support and education. Evidence suggests that comprehensive institutional mental health services, curriculum reforms, peer mentoring, faculty support, stress management training, regular physical activity, and digital literacy programs can substantially improve student well-being. Promoting responsible social media use and healthy digital habits, alongside accessible psychological support, may strengthen resilience and reduce burnout. A holistic, student-centered approach is essential to foster mental well-being, optimize academic performance, and prepare resilient future physicians capable of delivering high-quality patient care.